MDLText applied to automatic filtering of SPIM and SMS Spam - Silva, Renato Moraes; Almeida, Tiago A.; Yamakami, Akebo (iSys - Journal of Information Systems, 2018)
Spam filtering in online instant messages and SMS is a challenging problem nowadays. It is because the messages are often very short and rife with slangs, idioms, symbols, emoticons, and abbreviations which hamper predicting and knowledge discovering. In order to face this problem, we evaluated a simple, fast, scalable, multiclass, and online text classification method based on the minimum description length principle. We conducted experiments using a real and public dataset, which demonstrate that our method is effective on instant messaging and SMS spam filtering in both online and offline learning contexts.